Recent Patents in Imaging of the Vulnerable Atherosclerotic Plaque: The Search for the Holy Grail - Lupi, Alessandro; Rognoni, Andrea; Lazzero, Maurizio; Fattori, Rossella; Benedictis, Mauro D.; Sheiban, Imad; G. Secco, Gioel; S. Bongo, Angelo (Recent Patents on Medical Imaging (Discontinued), 2014)
Coronary obstruction by thrombus, triggered by rupture-prone atherosclerotic plaques, is the leading cause of myocardial infarction and accounts for millions of deaths and invasive coronary revascularization procedures. Coronary plaques become vulnerable far before any hemodynamic effect, thus conventional diagnostic techniques based on the angiographic assessment of the coronary vessels or the induction of myocardial perfusion defects or ischemia fail to identify lesions with an adverse clinical evolution. In this review we report about the currently available imaging methods used to investigate atherosclerotic plaques. Different coronary vessel imaging modalities such as coronary angiography, coronary ultrasound, nuclear imaging, magnetic resonance (MRI), computed tomography and other novel currently investigated methods are discussed in our systematic revision. Virtual histology IVUS, elastography and palpography are ultrasound-based methods used to characterize functions of different tissues their harmonic properties or their deformabilities. Optical coherence tomography, near infrared spectroscopy and fluorescence use infrared light to obtain high definition images of the vessel wall or tissue characterization. Intravascular MRI is a promising tool coupling high tissue-specificity imaging of MRI and high definition of intravascular techniques. Moreover recent advances in plaque-specific contrast media for magnetic resonance and positron emission tomography are described, highlighting their strength, pitfalls and future direction of the Research in the field. This article presents the current status in the technical background of intravascular ultrasound and nuclear tomographic imaging in the areas of clinical practice, and focuses on future developments of related patent forms.
Keywords: IVUS